2022
DOI: 10.1186/s13148-022-01418-0
|View full text |Cite|
|
Sign up to set email alerts
|

HTRA1 methylation in peripheral blood as a potential marker for the preclinical detection of stroke: a case–control study and a prospective nested case–control study

Abstract: Background Stroke is the leading cause of mortality in China. DNA methylation has essential roles in multiple diseases, but its association with stroke was barely studied. We hereby explored the association between blood-based HTRA serine protease 1 (HTRA1) methylation and the risk of stroke. Results The association was discovered in a hospital-based case–control study (cases/controls = 190:190) and further validated in a prospective nested case–co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Here, males have vascular risk factors more frequently than female CARASIL patients. In CARASIL, more than 50 symptomatic carriers have been reported, although most parents were asymptomatic [ 88 ]. For CARASIL, both gender and environmental factors may be involved, as strict risk factor control decreases the risk.…”
Section: Molecular Background and Possible Influencing Factorsmentioning
confidence: 99%
“…Here, males have vascular risk factors more frequently than female CARASIL patients. In CARASIL, more than 50 symptomatic carriers have been reported, although most parents were asymptomatic [ 88 ]. For CARASIL, both gender and environmental factors may be involved, as strict risk factor control decreases the risk.…”
Section: Molecular Background and Possible Influencing Factorsmentioning
confidence: 99%
“…32 Here, we detected the methylation level of DYRK4 in peripheral blood DNA in case-control studies to investigate the association between the methylation of DYRK4 and LC. Finally, the possible association between DYRK4 methylation and LC was validated in a nested case-control study based on the prospective Jurong Study which was described by Liu et al 33 Briefly, subjects recruited in the Jurong cohort were reported to be cancerfree at baseline. Seventeen subjects who developed LC within 2 years after the enrollment were included in the validation as pre-LC cases (average age 69.4 years), and 144 participants who remained cancer and cardiovascular disease-free during the 2.71-year follow-up time were selected as controls (average age 67.6 years).…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors have realized that ethics statement and Acknowledgement Section are incomplete. The corrected ethics statement should read as follows:…”
mentioning
confidence: 99%